Elements of practical banking - Ituwe, C. E. (Ibadan : University Press, 1983)
One of the primary aims of the book is to provide the layman, especially the bank customer, a source of elementary knowledge of what the banking industry looks like and what it can offer; the high school and university students who are taking courses in banking and relates studies; the bank official who needs a good knowledge of the set-up of his own institution and the banking industry generally. The book is divided into three parts. Part I, Background to banking operations. Part II, Principles of banking. Part III, Appendices.
Bibliography: p. 260-261.
rpm 03/05/2018
Loans
Keywords: Banks and banking; Bank management; Banks and banking